Hepatitis C at presentation in a newly diagnosed infant with B Acute Lymphoblastic Leukemia - Qurratulain Shahood Ahmed; Zehra Fadoo; Kamran Sadiq; Sadaf Altaf (Elsevier, 2018)
We report the unique case of a nine-month old patient diagnosed with B- Cell Acute Lymphoblastic Leukemia also positive for Hepatitis C virus, genotype 3 and a high viral load. With no existent literature to guide treatment of Hepatitis C in context of Infant Leukemia, treatment with direct-acting antivirals was deferred. A conservative approach to Hepatitis C was sought while he was undergoing chemotherapy, with the expectation of a spontaneous viral clearance, as has been documented for a quarter of otherwise healthy infants. Keywords: Hepatitis C, Infant leukemia, Direct acting antivirals